The air circulation over disaster area in the High Tatras - OSTROŽLÍK, Marián; HURTALOVÁ, Taťjana; MATEJKA, František (Contributions to Geophysics and Geodesy, 2008)
On November 19, 2004 forest stands in the High Tatras were affected by wind throw. During a few hours of the extremely strong wind the forest on areas about 100 km2 was destroyed. Subsequently, one year later, wildfire broke out on a part of this affected area. After this disturbance the environment microclimatic conditions have changed. The new conditions in the High Tatras region are subject of the study from many scientific aspects. Meteorological monitoring enables to carry out microclimatic research under various vegetative surface conditions. Hourly values of the wind speed and the wind direction at the fire-area (FIRE site, φ = 49° 18′ N, λ = 20° 12′ E) in the months May, June, and July were used to study wind conditions. These data were performed by WindSonic sensor at four levels: 0.5 m, 1.0, 2.0, and 4.0 m above the earth's surface.